Katoneng-Katoneng Cawir Metua: A Cultural Expression of Karo Society - Bebas Sembiring; Torang Naiborhu (PANGGUNG, 2017)
ABSTRACT Katoneng-katoneng is a traditional song of Karo ethnic in North Sumatera composed spontaneously using repetitive melody with different lyrics depend on the context and situation (strophic logogenic). Used in various social and cultural activities of Karo society, one of them is for the cawir metua ritual (the death of a person deemed to have been in accordance with the ideals and expectances of Karo society).This research reviewed the textual signification of Katoneng-katoneng as the cultural expression of the owner society by using the art theory (performing art), ethnomusicology, semiotic, and anthropology. Field data collected by direct observation, interview, and recording. Qualitative method used by defining key informant, including traditional figure, sierjabaten (musician), perkolong-kolong (katoneng-katoneng singer) and user society.The result shows katoneng-katoneng is the expression of various things: messages and advices, prayer, expectance, ideals, exemplary, life persistence, cooperation values, purpose of life, and others; delivered by perkolong-kolong professional singer represents those who have died and the elements of sangkep nggeluh (rakut sitelu) relatives by singing. The significance of the texts refer to culture ideals and concepts of Karo society.Keywords: katoneng-katoneng, cawir metua, sierjabaten, perkolong-kolong, sangkep nggeluh (rakut sitelu) ABSTRAK Katoneng-katoneng adalah nyanyian tradisional etnik Karo di Sumatera Utara yang diciptakan secara spontan menggunakan melodi tetap namun dengan teks baru sesuai situasi dan konteksnya (strophic logogenic). Digunakan dalam berbagai aktivitas sosial budaya masyarakat Karo, salah satunya ialah pada upacara cawirmetua (kematian seseorang yang dipandang telah sesuai dengan cita-cita dan harapan masyarakat Karo). Penelitian ini mengkaji fungsi dan makna tekstual katoneng-katoneng sebagai ekspresi kultural masyarakat pemiliknya dengan menggunakan teori kesenian (seni pertunjukan), etnomusikologi, semiotika, dan antropologi. Pengumpulan data lapangan dilakukan melalui pengamatan langsung, wawancara, dan perekaman. Menggunakan metode kualitatif dengan informan kunci yaitu tokoh adat, sierjabaten (pemusik), perkolong-kolong (penyanyi katoneng-katoneng) dan masyarakat pemiliknya. Hasil yang diperoleh menunjukkan bahwa katoneng-katoneng adalah ungkapan tentang berbagai hal: pesan-pesan dan nasehat, do’a, harapan, cita-cita, keteladanan, keteguhan hidup, nilai-nilai kegotong-royongan, tujuan hidup di dunia, dan lainnya yang disampaikan oleh penyanyi professional perkolong-kolong mewakili orang yang meninggal dan unsur-unsur kerabat sangkep nggeluh (rakut sitelu) dengan cara bernyanyi. Fungsi dan makna teks mengacu kepada cita-cita dan konsep-konsep budaya Karo.Kata kunci: katoneng-katoneng, cawir metua, sierjabaten, perkolong-kolong, sangkep nggeluh (rakut sitelu).